PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 98 PEKANBARU - Sumarni '; Gustimal Witri; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background problem in this research is student learning outcomes are still low, students are less active in learning, students tend to be relaxed in accepting learning and less motivated students in mathematics learning because learning methods only use the discouse method. CTL approach are more motivated the students to learn because the learning directly linked to students' daily lives. Students are also more active in the learning activities because students to learn with the group. Therefore, by learning together will cover the deficiencies of students in the group can be covered by other students who have excess. The research is in the form of classroom action research (PTK) with research subjects third grade students of SD Negeri 98 Pekanbaru totaling 32 students. The purpose of this research was to determine the improvement of student learning outcomes after application of CTL approach in mathematics class III SD Negeri 98 Pekanbaru. The data in this research is the quantitative data obtained from the data on the activities of teachers and students through observation and data tests students' knowledge and understanding through daily repetition cycle I and II. The results of this research showed that the average percentage of activity the teachers for implementing the learning activities increased from 83.93% (Good) in the first cycle to 92.86% (Very Good) in the second cycle. And the average percentage of student activity for implementing the learning activities increased from 83.93% (Good) in the first cycle to 91.08% (Very Good) in the second cycle. The average student learning outcomes seen from the test results of students has increased from Basic Scores obtained an average of 70.69. at UH I increased by 3.06 points to 73.75. And at UH II increased again to 8.75 points to 82.5. Overall there was an increase of Fundamental UH III scores by 11.81 points (16.19%). While classically reaching KKM on Basic Score is 40.63%. An increase in UH I as much as 15.62% to 56.25%. And increased again at UH II as much as 28.13% to 84.38%. So it can be concluded that the application of CTL approach can improve learning outcomes third grade students of SD Negeri 98 Pekanbaru. Key Word : CTL Approach, mathematics learning outcomes